ANALISIS KUALITATIF KANDUNGAN SAKARIDA DALAM TEPUNG DAN PATI UMBI GANYONG (Canna edulis Ker.) - Aprilia Kusbandari (Pharmaciana, 2015)
Canna Tubers (Canna edulis Ker.) is one of the plants producing carbohydrates. Its  also contains of protein, fat, vitamins, minerals,  phosphorus, iron and more calciums. The purpose of  this study is to identify of  sugar  in the powder and starch from canna tuber is a hydrolysis and didn’t hydrolysis. The method of qualitative analysis with tube test  and  Thin Layer Chromatography (TLC). The result indicated that before hydrolysis  canna powder  gave  sucrose (Rf = 0.45) and mannose (Rf=0.51), while after hydrolysis it gave  glucose (Rf=0.44), fructose (Rf=0.61) and mannose (Rf=0.51). In addition, canna starch gave   glucose (Rf=0.44) and maltose (Rf=0.35).